Theoretical Paradigm on Bank Capital Regulation and its Impact on Bank-Borrower Behavior - Bhatta, Gunakar (NRB Economic Review, 2015)
Bank equity plays an important role in the credit allocation process of financial intermediaries. Financial institutions with higher level of equity are in better position to absorb losses and repay deposits in a timely manner. This relates to the bank capital channel of monetary policy transmission mechanism stating that banks having sound financial health could contribute significantly in transmitting monetary impulses to the real sector. Considering the important role that bank equity plays in shaping the risk taking behavior of financial intermediaries, central banks set the minimum paid-up capital requirement for banks and financial institutions. Though this regulatory requirement is aimed at ensuring the smooth financial intermediation, this could become costlier in extending loans particularly in the times of business cycle fluctuations. A higher capital requirement might also constrain the lending capacity of a bank. Given the conflicting theoretical assumptions on the role of equity capital on financial stability and economic growth, this paper develops a theoretical model examining the relationship between bank equity and its effect on bank-borrower behavior. The theoretical model recommends that higher level of bank equity might be helpful in ensuring financial stability by altering the behavior of the bank and borrower.